Observations on nematodes from the Indonesian shortfin eel Anguilla bicolor bicolor McClelland in India, including a revalidation of Heliconema ahiri Karve, 1941 (Physalopteridae) - Moravec, František; Sheeba, Sarasamma; Kumar, Appukuttannair Biju (Acta parasitologica, 2013)
Two species of parasitic nematodes, Heliconema ahiri Karve, 1941 (Physalopteridae) and Procamallanus (Spirocamallanus) anguillae Moravec et al., 2006 (Camallanidae), were recorded from the Indonesian shortfin eel Anguilla bicolor bicolor Mc-Clelland in the Chalakkudi River and Veli Lake, respectively, both Kerala, India. The former species (H. ahiri), rediscovered from eels in India after 82 years from its original description, has been redescribed and revalidated based on its specific feature (presence of groups of minute denticles in the mouth) distinguishing it from other congeners; its finding in A. b. bicolor represents a new host record. The latter species (P. anguillae) has been recorded in India for the first time. SEM examination of its first-stage larvae from uterus has shown that P. anguillae is another species of Procamallanus whose larvae possess a crown of digit-like processes at the tail tip.
Keywords: India; Larva; nemoci ryb; Anguilla; Animals; Nematode Infections; Microscopy, Electron, Scanning; Indie; Spirurida; zvířata; mikroskopie elektronová rastrovací; Fish Diseases; nematodózy; larva